2013
DOI: 10.1016/j.adolescence.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding loneliness during adolescence: Developmental changes that increase the risk of perceived social isolation

Abstract: Loneliness is typically defined in terms of feeling states. In this review, we take a somewhat different approach, describing loneliness in terms of perceived social isolation. Vulnerabilities to perceived social isolation differ across the lifespan. Unique properties of adolescence are identified that carry special risk for perceived social isolation. These include (but are not limited to) developmental changes in companions, developmental changes in autonomy and individuation, identity exploration, cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
191
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(203 citation statements)
references
References 57 publications
2
191
1
9
Order By: Relevance
“…An early study in this area found that loneliness was associated with greater sleep problems in early and middle adolescents but not in later adolescents (Mahon 1994), perhaps because of the increasing prioritization of friends as sources of peer support in early/mid-adolescence (Helsen et al 2000). Indeed, adolescents are more likely to experience loneliness in early adolescence as opposed to late adolescence (Ladd and Ettekal 2013), which may accentuate the experience of social isolation (Laursen and Hartl 2013). Further, loneliness may contribute to increased depressive symptoms and social anxiety (Fontaine et al 2009;Lasgaard et al 2011;Storch et al 2003), which in turn may interfere with optimal sleep functioning.…”
Section: Peer Factorsmentioning
confidence: 99%
“…An early study in this area found that loneliness was associated with greater sleep problems in early and middle adolescents but not in later adolescents (Mahon 1994), perhaps because of the increasing prioritization of friends as sources of peer support in early/mid-adolescence (Helsen et al 2000). Indeed, adolescents are more likely to experience loneliness in early adolescence as opposed to late adolescence (Ladd and Ettekal 2013), which may accentuate the experience of social isolation (Laursen and Hartl 2013). Further, loneliness may contribute to increased depressive symptoms and social anxiety (Fontaine et al 2009;Lasgaard et al 2011;Storch et al 2003), which in turn may interfere with optimal sleep functioning.…”
Section: Peer Factorsmentioning
confidence: 99%
“…Adolescence is identified as a period of life when loneliness is particularly relevant, and there are some theorists who suggest that adolescent experience of loneliness may be different from that of children and adults, given developmental changes in identity, autonomy, and individuation as well as social perspective taking in adolescence (Heinrich & Gullone, 2006;Laursen & Hartl, 2013). The primary aim of the current study was to investigate social connectedness as a protective factor against loneliness and depression from early to middle adolescence.…”
Section: Overview Of Findings Within the Context Of The Literaturementioning
confidence: 99%
“…It has been argued (Asher & Paquette, 2003) that loneliness may be a normative experience as adolescents undergo significant changes in social roles, expectations, and identity (Laursen & Hartl, 2013). Loneliness, despite its prevalence during adolescence, still has the potential to be deleterious.…”
Section: The Relationship Between Loneliness and Depressive Symptomsmentioning
confidence: 99%
“…Therefore, the problems or issues in the network of social relations during adolescence can negatively affect one's life and cause them to feel alone.In the literature, it is said that adolescents are influenced more quickly from negative emotional states such as depression and loneliness. The risk of loneliness during adolescence is more severe because of the changes in the experience of physical and social isolation, and because each one is perceived at different levels by the adolescents (Laursen & Hartl, 2013). In this context, many changes in adolescence can bring about differentiation of the adolescent in self development and social relations.…”
Section: Discussionmentioning
confidence: 99%